Microstructure and wear of iron-based hardfacings reinforced with in-situ synthesized TiB2 particles - Kaptanoglu, M.; Eroglu, M. (Redakcia Kovove Materialy, 2017)
In this study, four hardfacings, reinforced with in-situ synthesized TiB2 particles, were cladded by tungsten inert gas (TIG) welding, applying flux-cored wires with varying Fe-Ti and Fe-B content. Microstructural examination, macrohardness and microhardness measurements and abrasive wear tests were performed. Morphology of TiB2 changed from a small-sized hexagonal and rectangular to a coarse plate-like one with the increasing common proportion of titanium and boron. Accordingly, hardness and wear resistance increased linearly with the changing titanium and boron content in hardfacings.
Keywords: TiB2; wear; microstructure; hardfacing; flux-cored wire